Magic, science, and the historiography of science - Joseph, Jacques (Dějiny – teorie – kritika, 2023)
The study aims to map the changes in the understanding of the relationship between magic and science during the 20th century. It draws on the positivist notion that regards magic as the irrational counterpart of science. Using Lynn Thorndike and Frances Yates as examples, this article shows how this idea was gradually undermined in historical research. Despite these developments and the gradual rehabilitation of the study of the history of Western esotericism in the late 20th century, the history of magic remains a somewhat problematic topic within academia. Current efforts to remedy this situation are represented by John Henry who is introduced at the end of the paper. In his conception, the notions of “magic” and “science” are stripped of any essentialist character, and the focus turns instead to the complex network of interactions, within which their boundaries are negotiated and rethought during the 16th-18th centuries. This view of the relationship between magic and science in the early modern period also shows how this construction of clear distinctions between the given fields laid the foundations for the positivist notion of the radical opposition between magic and science.